Fabricating of multi-interfacial charge transfer paths in the novel noble-metal-free Ni2P/ZnS/g-C3N4 ternary nanocomposite for enhanced charge separation and transfer for photocatalytic H2 generation - Rameshbabu R.; Paw J.K.S.; Ajaijawahar K.; Vinoth V.; Jadoun S.; Pugazhenthiran N.; Kiong T.S. (Elsevier Ltd, 2025)
This work reports the development of a novel Ni?P/ZnS/C?N? ternary nanocomposite photocatalyst for efficient hydrogen (H?) production. The nanocomposite was synthesized using a facile approach combining hydrothermal synthesis, ball milling, and wet impregnation methods then characterized using various techniques. Photocatalytic H? generation was evaluated under simulated solar irradiation with sodium sulfite (Na?SO?)/sodium sulfide (Na?S) as sacrificial reagents. The optimized 3NP/ZnS-8CN (3% Ni2P/ZnS/8% C3N4) catalyst displayed an exceptional H? generation rate of 3991 mol h?? g??, exceeding both pristine g-C3N4 (by 10.2 times) and 3% Ni2P/ZnS (by 1.2 times). This represents the highest reported rate of H? evolution for a graphitic carbon nitride (g-C3N4) based ternary nanocomposite under simulated solar radiation. Furthermore, the 3NP/ZnS-8CN photocatalyst exhibited good stability over four reaction cycles. This study provides valuable insights for designing efficient noble metal-free g-C3N4-based photocatalysts, which can significantly contribute to the transition to solar-driven hydrogen generation. The results of this study suggest that the synthesized composite materials hold significant promise for the advancement of new energy technologies. ? 2024 Elsevier B.V.